Temperature Affects Musculoskeletal Development and Muscle Lipid Metabolism of Gilthead Sea Bream (Sparus aurata) - Balbuena-Pecino, Sara; Riera-Heredia, Natàlia; Vélez, Emilio J.; Gutiérrez, Joaquim; Navarro, Isabel; Riera-Codina, Miquel; Capilla, Encarnación (Frontiers in Endocrinology, 2019)
World population is expected to increase to approximately 9 thousand million people by 2050 with a consequent food security decline. Besides, climate change is a major challenge that humanity is facing, with a predicted rise in mean sea surface temperature of more than 2 ºC during this century. This study aims to determine whether a rearing temperature of 19, 24 or 28 ºC may influence musculoskeletal development and muscle lipid metabolism in gilthead sea bream juveniles. The expression of growth hormone (GH)/insulin-like growth factors (IGFs) system-, osteogenic-, myogenic- and lipid metabolism-related genes in bone and/or white muscle of treated fish, and the in vitro viability, mineralization and osteogenic genes expression in primary cultured cells derived from bone of the same fish were analyzed. The highest temperature significantly down-regulated igf-1, igf-2, the receptor igf-1ra, and the binding proteins igfbp-4 and igfbp-5b in bone, and in muscle, igf-1 and igf-1ra, suggesting impaired musculoskeletal development. Concerning myogenic factors expression, contrary responses were observed, since the increase to 24 ºC significantly down-regulated myod1 and mrf4, while at 28 ºC myod2 and myogenin were significantly up-regulated. Moreover, in the muscle tissue, the expression of the fatty acid transporters cd36 and fabp11, and the lipases lipa and lpl-lk resulted significantly increased at elevated temperatures, whereas β-oxidation markers cpt1a and cpt1b were significantly reduced. Regarding the primary cultured bone-derived cells, a significant up-regulation of the extracellular matrix proteins on, op and ocn expression was found with increased temperatures, together with a gradual decrease in mineralization along with fish rearing temperature. Overall, these results suggest that increasing water temperature in this species appears to induce unfavorable growth and development of bone and muscle, through modulating the expression of different members of the GH/IGFs axis, myogenic and osteogenic genes, while accelerating the utilization of lipids as an energy source, although less efficiently than at optimal temperatures.